PENTINGNYA PEMBENTUKAN UNDANG-UNDANG LINTAS TRANSIT DI SELAT MALAKA BAGI INDONESIA DAN MALAYSIA - Muhammad Nasir (Faculty of Law, Universitas Diponegoro, 2013)
Indonesia and Malaysia are bordering contries the Malacca Strait which has been ratified by UNCLOS in 1982. Found in the UNCLOS 1982 transit Passage in the Malacca Stra;t not including the te